PERTUMBUHAN SPASIAL KLASTER INDUSTRI KECIL DI WILAYAH PERI-URBAN YOGYAKARTA - , RESHINTA H ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Peri-urban area is considered as an interface between rural and urban area. This area has mixed rural and urban characteristic which is reflected by land conversion from agricultural to industrial and settlement land use. Carter (1981) explained that industries in the peri-urban area are big scale industries which require large areas of land with long production process. Besides, there are also smaller scale industries which grow in the peri-urban area of Yogyakarta. These industries stimulate the development of small scale industries with common characteristic and create cluster area afterwards. Malmberg and Maskell (2001) noted the analysis of spatial clustering bring the fore concepts such as proximity, space, place, and milieu. These concepts become the focal points for research in economic geography. The aim of this research is to portray the spatial growth of these small scale industries and to identify the factors causing their growth in the peri-urban area of Yogyakarta. This research was carried out through exploratory case study, with field survey and interview. The business owners in each industrial cluster were participated in order to collect the data with purposive and stratified random sampling. The pattern of the clusterâs spatial growth analysis is performed by mapping the growth of the business each year. The influence factors analysis is done by analyzing the clusterâs history, growth, and patterns formed. From this research, can be concluded that the industrial clusterâs growth is widely related to the early stage of the cluster. The cluster grows and develops through some similar cluster development steps, emergence, growth, and sustainment. The pattern of each cluster industry in peri-urban area has different characteristic, but it tends to be linier and spreading all over the neighborhood area. The main factor that influence the industrial cluster growth is the external economies aspect. It is built by the spatial proximity of the cluster and the joint action done by the business owners. They enable the knowledge and skills transfer to happen so innovation of the cluster may be increased. Industrial cluster in the peri-urban area gets benefit from good access to information and the short distance to cities. Moreover, the rural society has harmonious and cooperative characteristic which highly encourage the clusterâs growth. Keywords: Spatial Growth, Small-Scale Industries, Industrial Cluster, Peri-Urban, Yogyakarta